Numerical Solution of Reliability Index based on Performance Evaluation for Yola Electrical Distribution Company - P.J Manga,; Mohammed Maina,; R.O Amusat,; S.D Buteh,; Garba Ibrahim, (Journal of Power Electronics and Devices, 2023)
A steady power system in the power sector is a way of meeting the energy demand of customers, to achieve this; there is a need to measure the level of interruption which contributes greatly to unreliability that faltered the business of the power industry. The effect of the interruption associated with the university, Bulumkutu, and Water treatment board of Yerwa Business Unit Distribution Maiduguri, Borno State said to affect likely most businesses situated in the aforementioned locations led to a reduction in economic viability and waste of billions of Naira. In this study, we made use of reliability indices to obtain its numerical solution based on the Institution of Electrical and Electronic Engineer (IEEE), to determine the level to which the performance of the system can serve and maintain the continuity of distribution of electrical energy to customers. The numerical results show that customers connected to Bulumkutu had the highest probability of power outage while the University and water treatment board had the lowest power outage. This clearly shows that the Bulumkutu energy distribution network is unreliable. This implies that Yerwa Business Unit distribution needs to improve operations and maintenance to meet the energy demand of the aforementioned locations.